E-LEARNING AND APPLICATION MECHANISMS WITH THE BEGINNING OF A CRISIS (COVID-19) IN IRAQ AL-MUTHANNA UNIVERSITY AS A MODEL - Ali Abd Al Razaq Alaboody; Asmaa Abdul Wahid Malik; Khariya abed fadel; Muslim jabbar jundi (Journal Park Publishing, 2024)
E-learning is of great importance in light of the rapid developments that the world is experiencing today, and its application in our present time represents a realistic, important and necessary matter, especially after the spread of the epidemic (COVID-19A curfew was imposed in most cities, governmental and private institutions, and all public and private sectors. Therefore, a new challenge has emerged, which is the application of the e-learning system in various educational organizations in Iraq, despite the lack of sufficient preparation for that. Therefore, this research came to reveal the reality of e-learning. In Iraq in general and at Al-Muthanna University in particular, with an explanation of the most important challenges that faced its application through an applied field study that included (15) Fifteen colleges distributed between scientific and humanities colleges to address the reality of e-learning in Iraq and in the university sample of the research in particular by collecting statistics and data on the most important procedures and activities implemented by the university in light of this. The research also aims to form an integrated picture of how to advance e-learning in the university under study. And presenting recommendations that contribute to achieving that goal. This research consists of four sections, the first includes the research methodology, the second represents the theoretical side of the research, while the third section includes the practical side of it, and the fourth section presents the most important conclusions and recommendations.
Keywords: COVID-19, E-learning, Al-Muthanna University.